2016
DOI: 10.21037/tau.2016.10.02
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy and the heart: friend, foe or bystander?

Abstract: The role of testosterone therapy (TTh) in cardiovascular disease (CVD) outcomes is still controversial, and it seems will remain inconclusive for the moment. An extensive body of literature has investigated the association of endogenous testosterone and use of TTh with CVD events including several meta-analyses. In some instances, a number of studies reported beneficial effects of TTh on CVD events and in other instances the body of literature reported detrimental effects or no effects at all. Yet, no review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Testosterone is linked to many physiologic effects, including improved sexual function, physical performance, muscle strength, lean body mass and cognitive function . Low levels of testosterone are associated with cardiovascular diseases, cancer and all‐cause mortality . Surprisingly, in the last decade, studies have shown that as many as 38.7% of men over 45 years old demonstrate low levels of testosterone (testosterone deficiency [TD]; total testosterone ≤350 ng/dL [12.15 nmol L −1 ]) .…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone is linked to many physiologic effects, including improved sexual function, physical performance, muscle strength, lean body mass and cognitive function . Low levels of testosterone are associated with cardiovascular diseases, cancer and all‐cause mortality . Surprisingly, in the last decade, studies have shown that as many as 38.7% of men over 45 years old demonstrate low levels of testosterone (testosterone deficiency [TD]; total testosterone ≤350 ng/dL [12.15 nmol L −1 ]) .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there has been a small number of studies investigating the link between phosphorous and T levels. However, this link merits further scrutiny because high levels of phosphorous has been associated with a high risk of cardiovascular diseases [47], but low levels of T has been linked to a higher risk of cardiovascular disease [4,48]. A community dwelling study of 1,346 older men reported that high serum T levels were associated with lower serum phosphorus levels in a model adjusted for age, race and estradiol levels [49].…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone (T) is linked with many physiologic effects, including improved sexual function, physical performance, muscle strength, lean body mass, cognitive function and an increased risk of cardiovascular mortality and morbidities [1][2][3]. Low levels of T is associated with cardiovascular diseases [4], cancer [5] and all-cause mortality [6]. In the United States alone, studies have reported that as many as 38.7% of men 45 years or older demonstrate low levels of T [7,8] or T deficiency (total testosterone ≤ 350 ng/dL) [9] with a projection that by 2025 approximately 6.5 million men will have T deficiency [8,10].…”
Section: Introductionmentioning
confidence: 99%
“… 21 In late 2013 and early 2014, two studies reported increased myocardial infarction and stroke associated with TTh use 22 , 23 ; however, other studies investigating the relationship between endogenous/exogenous testosterone and CVD in systematic reviews and meta-analysis of observational studies and randomized controlled trials found inconclusive results. 24 Of interest, there is a potential biological plausibility in the interaction between cholesterol and testosterone, and with their treatments, statins and TTh, because cholesterol is a required intermediate precursor in steroidogenesis. 25 27 Therefore, the objective of this study is to investigate the independent and joint associations of statins and TTh with CVD among HRCa survivors and a matched cancer-free cohort.…”
Section: Introductionmentioning
confidence: 99%